Evaluation of automatic tube current modulation of CT scanners using a dedicated and the CTDI dosimetry phantoms - Ioannis A. Tsalafoutas (14776939) (2023)
Evaluation of automatic tube current modulation of CT scanners using a dedicated and the CTDI dosimetry phantoms Other Information Published in: Journal of Applied Clinical Medical Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/acm2.13620